2021
DOI: 10.1002/cam4.4511
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes the tolerogenic phenotype of plasmacytoid dendritic cells in head and neck squamous cell carcinoma

Abstract: Objective We aim to review the roles of plasmacytoid dendritic cells (pDCs) in head and neck squamous cell carcinoma (HNSCC) and explore the effects of hypoxia on the tolerogenic transformation of pDCs. Background pDCs, best known as professional type I interferon‐secreting cells, play key roles in immune surveillance and antitumor immunity. Recently, pDCs have been shown to be tolerogenic and correlate with poor prognosis in a variety of cancers, including HNSCC. However, it remains unclear what drives the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…HIF-1α is a negative regulator of pDC differentiation in vitro and in vivo [ 223 ]. In head and neck squamous cell carcinoma (HNSCC), a hypoxic TME promoted pDC migration through the HIF-1α/CXCL12/CXCR4 pathway and induced the acquisition of a tolerogenic pDC phenotype, which was characterized by defective production of IFN-α, reduced antigen presentation abilities, and expansion of Treg cells [ 224 ]. In cervical cancer, hypoxia upregulated HMGB1 release, leading to TLR9-mediated inhibition of pDC maturation and cytokine secretion and the generation of tolerogenic pDCs [ 225 ].…”
Section: Immunosuppressive Role Of the Tme On DC Functionsmentioning
confidence: 99%
“…HIF-1α is a negative regulator of pDC differentiation in vitro and in vivo [ 223 ]. In head and neck squamous cell carcinoma (HNSCC), a hypoxic TME promoted pDC migration through the HIF-1α/CXCL12/CXCR4 pathway and induced the acquisition of a tolerogenic pDC phenotype, which was characterized by defective production of IFN-α, reduced antigen presentation abilities, and expansion of Treg cells [ 224 ]. In cervical cancer, hypoxia upregulated HMGB1 release, leading to TLR9-mediated inhibition of pDC maturation and cytokine secretion and the generation of tolerogenic pDCs [ 225 ].…”
Section: Immunosuppressive Role Of the Tme On DC Functionsmentioning
confidence: 99%
“…31 The malignancy of HNSCC relies on hyperactivated glycolysis to meet the energetic and biosynthetic demand. 32,33 In this study, we developed a robust risk score model using 12 GHRGs to predict the prognosis of HNSCC patients, which have potential for use in clinical manifestations for convenient prognostic monitoring. Currently, a plethora of studies have established the mechanistic interplay between glycolysis/hypoxia and HNSCC, which sheds light on the prognostic prediction of HNSCC using glycolysis/ hypoxia genes.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma is one of the most prevalent cancers globally, characterized by its uncontrolled aggressiveness and unfavorable prognosis 31 . The malignancy of HNSCC relies on hyperactivated glycolysis to meet the energetic and biosynthetic demand 32,33 . In this study, we developed a robust risk score model using 12 GHRGs to predict the prognosis of HNSCC patients, which have potential for use in clinical manifestations for convenient prognostic monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the dominance of CD11c + subset in renal inflammation, we used CD11c + DCs‐deficient mice to explore the mechanism of immune tolerance induced by CD11c + DCs. In recent years, studies have shown that Tol‐DCs play a crucial role in the treatment of various inflammatory diseases, such as autoimmune disorders, tumors, heart and kidney transplantation 10,38–40 . DC vaccine as an immune therapy in cancer and organ transplantation has made significant progress, 41,42 but the research in AKI is still lacking.…”
Section: Discussionmentioning
confidence: 99%